2009
DOI: 10.1590/s0100-06832009000600031
|View full text |Cite
|
Sign up to set email alerts
|

Estoques de carbono orgânico e de nitrogênio no solo em sistema de integração lavoura-pecuária em plantio direto, submetido a intensidades de pastejo

Abstract: RESUMOSistemas de integração lavoura-pecuária têm um alto potencial de uso no sul do país, especialmente em áreas de soja sob plantio direto, com espécies de cobertura no inverno. A condução de sistemas de integração com diferentes intensidades de manejo da pastagem resultará, ao longo do tempo, em estoques de C orgânico (CO) e de N diferenciados, decorrentes do aporte diferenciado de resíduos. Este trabalho foi realizado para avaliar a evolução dos estoques de CO e de N total (NT) e em frações físicas da maté… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0
45

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 10 publications
(9 reference statements)
2
41
0
45
Order By: Relevance
“…However, the period of establishment of the system may be a determining factor. Souza et al (2009) observed C losses at a high grazing intensity (10 cm), and C increases at moderate grazing intensities (20 and 40 cm) or with no grazing following three years of ICL with no tillage.…”
Section: Resultsmentioning
confidence: 75%
“…However, the period of establishment of the system may be a determining factor. Souza et al (2009) observed C losses at a high grazing intensity (10 cm), and C increases at moderate grazing intensities (20 and 40 cm) or with no grazing following three years of ICL with no tillage.…”
Section: Resultsmentioning
confidence: 75%
“…The main constituents of SOM are C (52-58 %) and N (3.7-7 %); the soil levels and pools of these elements vary according to the application rates of plant and animal residues and to the losses resulting from erosion and oxidation by soil microorganisms (Souza et al, 2009). SOM is involved in the balance between the C and N cycles, and its content is stable in soils under native vegetation (Bortolon et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In traditional agricultural systems tillage is usually more intense, leading to erosive losses and increased microbial activity due to the greater exposure of organic residues to microorganisms and their enzymes Souza et al, 2009). These conditions result in decreased levels of C and N and, consequently, increased C-CO 2 emissions into the atmosphere and decreased N cycling (Sharma et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations